Essential University Physics: Volume 1 (3rd Edition)

Published by Pearson
ISBN 10: 0321993721
ISBN 13: 978-0-32199-372-4

Chapter 13 - Exercises and Problems - Page 240: 62


Please see the work below.

Work Step by Step

As we know that $E=\frac{1}{2}mv^2+\frac{1}{2}kx^2$ We differentiate both sides to obtain: $\frac{dE}{dt}=\frac{1}{2}m\frac{d}{dt}v^2+\frac{1}{2}k\frac{d}{dt}x^2=0$ $\implies \frac{1}{2}m2v\frac{dv}{dt}+\frac{1}{2}2x\frac{dx}{dt}=0$ As $\frac{dx}{dt}=v$ and $\frac{dv}{dt}=a$ $\implies mva+kxv=0$ $v(ma+kx)=0$ $ma=-kx$ $\implies m\frac{d^2x}{dt}=-kx$ This is same as equation 13.3, hence proved.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.